2019
DOI: 10.3390/md17040243
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Anti-Adhesive Coating Based on an Extracellular Polymer from a Marine Cyanobacterium

Abstract: Medical device-associated infections are a major health threat, representing about half of all hospital-acquired infections. Current strategies to prevent this problem based on device coatings with antimicrobial compounds (antibiotics or antiseptics) have proven to be insufficient, often toxic, and even promoting bacterial resistance. Herein, we report the development of an infection-preventive coating (CyanoCoating) produced with an extracellular polymer released by the marine cyanobacterium Cyanothece sp. CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 50 publications
4
35
0
Order By: Relevance
“…CyanoCoating was previously characterized in terms of thickness and wettability [ 20 ]. However, since surface topography is known to impact biofilm development, this parameter was evaluated by atomic force microscopy (AFM).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CyanoCoating was previously characterized in terms of thickness and wettability [ 20 ]. However, since surface topography is known to impact biofilm development, this parameter was evaluated by atomic force microscopy (AFM).…”
Section: Resultsmentioning
confidence: 99%
“…However, since surface topography is known to impact biofilm development, this parameter was evaluated by atomic force microscopy (AFM). CyanoCoating and medical grade polyurethane (PU) were covalently bound through a polydopamine (pDA) layer to gold (Au) substrates, as previously described [ 20 ]. The deposition of either the pDA + CyanoCoating or the control pDA + PU increased significantly surface roughness of Au substrates, as depicted in Figure 1 A. CyanoCoating exhibited a smoother surface in comparison with PU, as demonstrated by the decrease of the average roughness (Ra) ( Figure 1 A 1 ) and the root mean square roughness (Rq) ( Figure 1 A 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, and as preliminary studies have shown, it has the versatility to be applied in different areas ranging from bioremediation to biomedicine; e.g. as a biosorbent for heavy metals bioremediation (Mota et al, 2016), as a vehicle for proteins or vitamins delivery (Estevinho et al, 2019;Leite et al, 2017;Mota, Tamagnini, Gales, Leite, & Pereira, 2018) and as anti-adhesive coatings (Costa et al, 2019). Moreover, the particular features of this carbohydrate polymer can be interesting for food and cosmetic industries, since similar polymers from other origins have been used as flocculants, thickening, hydrating, emulsifying and/or gelling agents, improving the product quality and texture.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%